Analisis Pengaruh Harmonik Terhadap Peningkatan Temperatur Pada Trafo Distribusi 3 Fasa 400 kVA Di Fakultas Teknik Universitas Riau. - Tumpak Dolok Stepan Simarmata; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Distribution transformer has an important role in the distribution of electric power in a distribution system. So that the transformer can operate with both the condition of the transformer must be in a stable condition. One of the things that can damage the transformer is non-linear load, such as computers, printers, air conditioning (AC) equipment lab in every department and equipment other electronics that may cause harmonic on the network power systems, content of harmonic high can cause a condition of distribution transformer overheats and if not treated immediately will cause transformer life time becomes shorter. This study aimsto determine the harmonic correlation to the increase of temperature on the distribution transformer in the Faculty of engineering University of Riau.Keywords : Non Linear, Harmonic, correlation